Chaos control via state-dependent riccati equation method applied a non-ideal vibration absorber coupled to a nonlinear oscillator - Chavarette, Fabio Roberto [UNESP]; Peruzzi, Nelson Jose [UNESP]; Da Costa Ferreira, Douglas; Lopes, Mara Lucia Martins (Academic Publications, 2015)
The non-ideal vibration absorber system coupled to a nonlinear oscillator is proposed in the paper. This system is demonstrated with a chaotic behavior and we present the control technical for the chaos stabilization. The simulation results show the effectiveness of the control strategy.
Keywords: Chaos Control; Non-Ideal System; State-Dependent Riccati Equation; Vibration